Challenges of Implementing Pancasila Values Among Millennials and Gen Z - Widya Anininda Rahma Suci; Dhinda Dwi Rahmadhani (Kawakib: Journal of Multidisciplinary Research, 2026)
Millennial and Gen Z generations face new challenges in understanding the principles of Pancasila due to technological advancements and globalization. Recent literature studies were used in this research to identify the main obstacles and approaches to promoting Pancasila values among the younger generation. The method used is to conduct a systematic review of publications published from 2020 to 2025 using keywords related to Pancasila, youth, digital literacy, and character education. This was done using databases such as Google Scholar, Garuda, and university e-journals. 36 articles from the initial 78 documents were selected and descriptively-qualitatively analyzed. The research results indicate that the biggest factors causing the decline in Pancasila values are social media, popular culture, low ideological literacy, poor character education, and public role models. However, the literature also suggests the possibility of strengthening thru project-based learning, which is valuable for digital literacy. The research results show that the biggest factors causing the decline in Pancasila values are social media, popular culture, low ideological literacy, poor character education, and public role models. However, the research also indicates that there is a possibility of strengthening thru project-based learning, beneficial digital literacy, multi-stakeholder collaboration, and the use of digital space as a means of campaigning for national values. In conclusion, for Pancasila to remain relevant in modern life, internalizing its values in the millennial and Gen Z generations requires an adaptive, contextual, and integrated approach.